Negative frequencies and negative norms in analogue Hawking radiation systems - Aguero-Santacruz, Raul; Bermudez, David (Comptes Rendus. Physique)
In this work, we study the core concepts of Hawking radiation in the astrophysical and analogue systems. We focus on negative frequencies and negative norms: their definition, their relationship, and their role in the particle creation process of the Hawking effect. We characterize the dispersion relation by the signs of the frequency and the norm. We conclude that the most natural frame for studying the Hawking effect is that in which the horizon is static, where the sign of the norm can be made equal to the sign of the Doppler-shifted frequency in that frame. We use as examples the four most successful experimental analogue systems: water waves, Bose–Einstein condensates, polaritons fluids, and optical fibers.